2022
DOI: 10.1186/s13075-022-02730-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics of popliteal lymphatic vessels and peripheral veins reveals altered lymphatic muscle and immune cell populations in the TNF-Tg arthritis model

Abstract: Background Lymphatic dysfunction exists in tumor necrosis factor transgenic (TNF-Tg) mice and rheumatoid arthritis (RA) patients. While joint-draining TNF-Tg popliteal lymphatic vessels (PLVs) have deficits in contractility during end-stage arthritis, the nature of lymphatic muscle cells (LMCs) and their TNF-altered transcriptome remain unknown. Thus, we performed single-cell RNA-sequencing (scRNAseq) on TNF-Tg LMCs in PLVs efferent to inflamed joints versus wild-type (WT) controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…In this work, we found that direct LMC damage may not be responsible for the reduced lymphatic function and onset of severe inflammatory-erosive arthritis in TNF-Tg mice. Alternative mechanisms, such as chemical inhibition of lymphatic contractility through the accumulation of peri-lymphatic inflammatory immune cells 22 or interactions with adjacent LECs 11 , ought to be investigated in future studies. Of particular relevance, NOS inhibition is effective in recovering lymphatic contractility in some studies 8 , 11 , 33 ,while recent investigation of global genetic iNOS ablation demonstrated limited effects on lymphatic function and arthritis progression in TNF-Tg mice 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we found that direct LMC damage may not be responsible for the reduced lymphatic function and onset of severe inflammatory-erosive arthritis in TNF-Tg mice. Alternative mechanisms, such as chemical inhibition of lymphatic contractility through the accumulation of peri-lymphatic inflammatory immune cells 22 or interactions with adjacent LECs 11 , ought to be investigated in future studies. Of particular relevance, NOS inhibition is effective in recovering lymphatic contractility in some studies 8 , 11 , 33 ,while recent investigation of global genetic iNOS ablation demonstrated limited effects on lymphatic function and arthritis progression in TNF-Tg mice 29 .…”
Section: Discussionmentioning
confidence: 99%
“…myosin heavy chain 11 (Myh11)) 36 or transcriptional changes (i.e. Zbtb16 ) 22 may have recovered during the treatment period associated with amelioration of arthritis. In addition, based on our unsuccessful prospero homeobox 1 (Prox1) staining (as previously performed 26 ) and lack of bona fide valve associated markers (i.e., integrin-α9 37 ), we were limited in our capacity to analyze specific PLV regions (i.e., valve vs non-valve).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the onset of Advanced arthritis and lymphatic dysfunction, these activated macrophages stagnate within the popliteal lymphatic vessels and PLN, and mediate tissue destruction and immune cell activation (Li et al, 2013). This lymphatic stagnation is associated with LEC (Bouta et al, 2017) and lymphatic muscle cell (LMC) (Jiao et al, 2022; Kenney et al, 2020; Kenney et al, 2022c; Liang et al, 2021) apoptosis and efferocytosis by joint-draining macrophages leading to intracellular iron accumulation (Fig. 6D).…”
Section: Discussionmentioning
confidence: 99%